From post-industrialism to border neoliberalism: Industrial Disctrict of Arica, second decade 21st century - Sánchez, Bastovino (2021)
We present an ethnographic case study on urban-border reconversion in Arica (Chile), concentrating on the industrial neighborhood of this city. This urban sector today shows contradictory tendencies between an post-industrialism and neoliberal socio-spatial functionality; given a growing combination of public neglect and real estate privatization. We postulate that this contradiction is still pending resolution, although its qualities are generating new inequalities and urban-border imaginary. We discuss all this based on local and regional research, with conceptions of Marxist urbanism.